ISLAMIC EDUCATION FOR SUSTAINING HUMANITY - Ahmad; Syarifuddin; Umar; Ramadhan, Syahru; Nazilla, Sazkia (LPPM STAI Muhammadiyah Probolinggo, 2024)
The nature of Islamic education is an effort or process to change human attitudes and behaviour based on the formulation of rules in its teachings. So that it is able to postulate Islamic teachings and translate them into positive and civilised practices. The purpose of this research is to examine the role and contribution of Islamic education for humanity. The method used is library research. The result is that Islamic education continues to transform in supporting humans to achieve a civilised life based on the Qur'an and as-Sunnah. Islamic education continues to purify its teachings and teachings starting from the form of practice from the conversion of traditional beliefs to rational beliefs, so that Muslims really return to the true authentic Islamic doctrine. Then in interpreting human existence in life, namely to carry out the task of caliphate on Earth which is given the title khalifatul fill ard by Allah SWT. As a continuation of the Divine mission, it aims to form a harmonious life in the world by sticking to the Koran as the basis for practice. In Islam also all forms of human life affairs have been given guidance through the Koran. To manifest these values, Islamic education is present as a support for humanity.